História pública: um caminho para o desenvolvimento sustentável do turismo ambiental e histórico no interior da Bahia - Nunes, Luciana de Lima Xavier (Universidade do Vale do Rio dos Sinos, 2023)
This monograph reflects the search for a connection between my two previous formations: Communication and Marketing, and my current academic trajectory in History. Experience in the advertising market, management in companies of different sizes, and work as a national and international consultant have shaped my professional path. However, growing restlessness led me to seek a more humanistic and sustainable approach, and I found in Public History - which extends beyond academic boundaries, impacting society in various ways - this anchoring. The decision to study History was not by chance. It arose from the need to theoretically ground the new worldview and professional choice, especially regarding the relationships between history, memory, and historiography. Awareness of more sustainable management practices, such as ESG (Environmental, Social, and Governance), along with the growing demand of new generations for life purposes and conscious consumption, motivated the adherence to humanism and corporate sustainability. One of the consultancy projects, “Bahia Viaja na Bahia”, which sees Public History as the bridge to this new management path, propels this monograph. This work aims to contribute to expanding discussions on the application of Public History in new contexts, laying the foundations for more inclusive, ethical, and socially responsible projects. By reflecting on Public History as a fundamental tool for humanistic and sustainable management, I hope to pave the way in the business consulting sector and contribute to a new space, beyond academia, for historians.
Keywords: História pública; Gestão humanista; Bahia; Turismo; ESG; Public history; Humanistic management; Tourism